A Systematic Literature Review and Bibliometric Analysis of Recycling Behavior. Issue 5 (19th October 2020) - Phulwani, Payal R.; Kumar, Divesh; Goyal, Praveen
Abstract: As society moves closer to sustainability, recycling becomes one of the core concepts of sustainable behavior. Recycling behavior research is receiving extensive attention from various disciplines because of the increasing prioritization of resource recovery and management by policymakers and industry. This article provides a clear view of the progression of publications and research diversification within the domain. The 788 articles which focused on consumers' or households' recycling behavior were analyzed using software. Resources, Conservation and Recycling was the top contributing journal, and Stewart Barr was the top contributing author. With the help of citation analysis and bibliographic coupling, the intellectual structure of recycling behavior research was obtained, showing that the research had diversified into seven identifiable clusters. The research in the area was initially focused on environmental behaviors and their determinants, household recycling behavior and behavioral theories like the Theory of Planned Behavior. Other focus areas that aid in research progression were spillover effects, past behavior, habits and behavior change. These clusters further provided the base for research on recycling behavior toward specific product categories. The content analysis of the lead papers in each cluster further helps in disclosing the foundations of and future directions of research.